Performance analysis of a trellis coded modulation spread spectrum system - Phoa, Ngee Kiat. (2009)
Spread spectrum comunications, with its inherent resistance to interference, have over the years become an increasingly popular technique for use in many different systems. Applications range from antijam systems, to code division multiple access systems, to systems designed to combat multipath. Recent studies have shown that coding the data before spreading can improve the performance of the system significantly. This project examined the performance of convolutionally coded and trellis coded spread spectrum systems under constant power broadband jamming and pulse jamming.